PENERAPAN NILAI-NILAI PENDIDIKAN AGAMA ISLAM MELALUI ORGANISASI IPNU – IPPNU (STUDI KASUS IPNU-IPPNU DI KECAMATAN LOWOKWARU) - Muchammad Sukma Andika; Kukuh Santoso; Muhammad Fahmi Hidayatullah (VICRATINA, 2022)
Nahdlatul Ulama Student Association & Nahdlatul Ulama Women's Student Association, commonly known as IPNU-IPPNU which is under the auspices of Autonomous Body Nahdlatul Ulama, IPNU-IPPNU Organization itself is at the level of coverage in society. Therefore, it can be reviewed here that the organization can provide Islamic religious education outside of formal schools. There is a lot of religious knowledge that is not obtained from school, but in organizations it can be easily obtained, even more. In this study using a qualitative approach. The data comes from words and actions using interview, observation, and documentation techniques. Analysis of the data obtained from reduction, presented and then drawn conclusions according to the purpose of this study. The results of this study are first, the implementation of the application of the values of Islamic religious education through activities such as routine reading of tahlil and istighosah, reading of the Prophet's birthday, and social service. Second, the value of Islamic religious education that is instilled such as the value of Aswaja (Ajlu Sunnah Wal Jamaah), the value of aqidah which is about belief in God Almighty, the value of Amaliyah, namely the value of worship or the implementation of the values of faith and morals. Third, the results of the application of Islamic religious education values carried out by the IPNU-IPPNU Lowokwaru organization can be seen from the personality attitudes of each member who are able to maintain ethics and socialize.